Metabolic Alterations in Aging Macrophages: Ingredients for Inflammaging?. Issue 2 (February 2019) - van Beek, Adriaan A.; Van den Bossche, Jan; Mastroberardino, Pier G.; de Winther, Menno P.J.; Leenen, Pieter J.M.
Abstract : Aging is a complex process with an impact on essentially all organs. Declined cellular repair causes increased damage at genomic and proteomic levels upon aging. This can lead to systemic changes in metabolism and pro-inflammatory cytokine production, resulting in low-grade inflammation, or 'inflammaging'. Tissue macrophages, gatekeepers of parenchymal homeostasis and integrity, are prime inflammatory cytokine producers, as well as initiators and regulators of inflammation. In this opinion piece, we summarize intrinsic alterations in macrophage phenotype and function with age. We propose that alternatively activated macrophages (M2-like), which are yet pro-inflammatory, can accumulate in tissues and promote inflammaging. Age-related increases in endoplasmic reticulum stress and mitochondrial dysfunction might be cell-intrinsic forces driving this unusual phenotype. Highlights: Aging is associated at the cellular level with several adaptations, fueled by increasing damage and reduced capacity for repair. This generates a condition of low-grade inflammation, called 'inflammaging'. Macrophages are prime cells in initiation and regulation of inflammatory processes and may thus play major roles in inflammaging. Macrophage polarization and activation, induced by intrinsic or extrinsic conditions, are reflected in and regulated by the cells' metabolic and epigenetic profiles. Age-induced changes in macrophages are diverse and, in general, may represent pro-inflammatory activation of cells with an alternatively activated (M2-like) phenotype.